Derivation, validation, and numerical implementation of a two-dimensional boulder transport formulation by coastal waves - Watanabe, Masashi (2022)
Numerical computations for boulder transport have become a state-of-the-art tool for hindcasting the hydraulic processes associated with past storm wave and tsunami events. Since most previously developed two-dimensional formulations cater to boulders with symmetric outlines, they can consequently reproduce the transport distance and the velocity of boulders of cubic shape or similar structured geometries reasonably well. However, the formulations exhibit limitations when applied to rectangular- and flat-shaped boulders. The presently available formulations have difficulties reproducing the variations of frictional drag force due to the changes of the boulders' contact time with the ground. We have developed an extended boulder transport formulation and derived a new empirical roughness coefficient by considering the shape of boulders that accounts for the changes of the boulders' contact time with the ground. In comparison to other existing transport formulations, the present method provides superior accuracy of block velocity and transport distance in most cases - especially for boulders of rectangular geometry. Even by neglecting the full three-dimensional processes, numerical computations extended with the proposed boulder transport formulation can help explaining historic wave regimes, which were responsible for the transport of a variety of coastal boulders reported around the world.